Fingerprint image watermarking in spatial, frequency and multiresolution domain: techniques and challenges - Lebcir, Mohamed; Suryanti, Awang (Universiti Malaysia Pahang, 2018)
Fingerprint biometric system has been used as a personal authentication in many fields including law enforcement, business, etc. Fingerprint digital watermarking technique is implemented to increase the fingerprint security in terms of its originality. Thus, a number of related research studies have been analyzed in this paper. Three embedding domains are more commonly studied which are spatial domain, frequency domain and the multiresolution domain. These are used to implement the watermarking technique in fingerprint images. The strength and weakness of each technique in these embedding domains are discussed in this paper. This paper is categorized based on the domains. The most appropriate domain to implement the digital watermarking in fingerprint image combines between frequency and multiresolution due to the two domain advantages. The challenges of the fingerprint digital watermarking implementation are discussed in this paper as well based on the finding of the strength and weakness. We can conclude that the main challenges of this implementation are blind and more robust against a geometric attack like translations or rotations with the aim to provide higher security and robustness without corrupting minutiae points. This is because the fingerprint features can be easily affected by the incorporated watermark. In addition, a different set of features may be introduced due to displacements and rotations of the fingerprints.